Menyingkap Situs "Koto Rayo", Pemukiman Kuno di Tepi Sungai Tabir Jambi - Pahrudin, Pahrudin (Unisia, 2012)
Sumatra Island have high civilization in the past, especially through The Kingdom of Sriwijaya that controled and dominated all around this island and most of South East Asia territories. One area of the Kingdom Sriwijaya’s territory in Sumatra Island is Jambi, that have many Kingdoms of Melayu before. ‘Koto Rayo’ that located at side of Tabir River may be one of the civilization that connected with history of Kingdoms of Melayu Jambi and Kingdom of Sriwijaya in the past. Because, the remnants of the past about Koto Rayo, like red bricks, are very resemble with red bricks of temple in other area at Jambi (Muaro Jambi Temple) and many stories about this site are connected with history of Jambi in the past. This article discusses about ‘Koto Rayo’, an ancient settlement at side of Tabir River. This site has been kept secret of Jambi and history that haven in this area in the past. Kata Kunci: Sumatra, Sriwijaya, Melayu, Jambi, Civilization, Koto Rayo.